(untitled) (Research, Society and Development, 2022)
The debate on sex education and associated topics is scarce within the school environment and has the potential for experiences that can harm the fullness of a healthy sexuality. Therefore, this work aimed to guide to reduce risk behaviors that compromise the expression of a healthy sexuality, free from sexually transmitted infections, unplanned pregnancy and abusive relationships. Initially, a questionnaire was applied to survey previous knowledge and, later, a School Intervention Guide on Sexual Education was built and implemented among students of the 1st year of high school at Liceu de Artes e Ofícios, located in Recife / PE. The questionnaire and the Guide were applied remotely through Digital Information and Communication Technologies (TDIC). Sexual Education, Prenatal Care, Teenage Pregnancy, Sexually Transmitted Infections and Machismo were the topics covered in the Intervention Guide. The questionnaire allowed us to identify that students believe that a sex education subject would be important for their school (96.6%), they think it is important for men to accompany women during prenatal care (98.9%), they know of any case of pregnancy among young people aged between 11 and 15 (86.2%), recognize the importance of contraceptive methods (100%), and think that women suffer from machismo (97.7%). The remote application of the Guide contributed to knowing safe information and questioning the themes worked in a biological-social approach. Extension actions on Sex Education are very relevant to inform and sensitize youth who experience the beginning of the expression of sexuality.